Analisis Karakteristik Pengguna Bus BSD Link Untuk Desain Koridor Baru Menggunakan Model Permintaan Perjalanan - Verdy Ananda Upa; Rahmat Setyadi (Politeknik Negeri Jakarta, 2020)
Bumi Serpong Damai (BSD) is one of self contained city in Jabodetabek district. Sinarmas as developer of BSD started to develope the Mass Rapid Transit which special operated on that. Concept of MRT has been operated in the form of Bus Rapid Transit. A new BRT corridor implementation need a Passenger Demand Prediction . Thus, a special BRT Passenger Demand Modelling Method for a new BRT Line need to be developed. This attempt needs knowledge on the Existing BRT User Trip Characteristics. BSD Link User Trip Characteristics Survey were executed on Corridor Sector 1.3 Greenwich Park, during morning peak hour. The result indicates that the BRT are used mainly for working (63%) and schooling (37%) trips, the BRT passengers are the previous public transport (45%) and motorcycle (55%) users. The trip origin zone is extended 1 km to the left and right of the BSD Link corridor, while the trip destination zone is extended 500 meters to the left and right of the BSD Link corridor. The embarking connecting trip modes are dominated by motorcycle (43%) and walking trip (57%), while the alighting connecting trip modes are dominated by motorcycle (16%) and walking trip (84%)